Interfacial construction and lattice distortion-triggered bifunctionality of Mn-NiS/Mn-Ni3S4 for H2 production. (15th November 2022) - Huang, Haoyu; Hu, Xin; Hou, Zhuoran; Yang, Di; Xiang, Dan; Hu, Liwen
Highlights: Mn-NiS/Mn-Ni3 S4 composite catalysts were successfully synthesized by using Ni(OH)2 as the precursor with Mn doping and sulfurization at low temperature. The successful doping of Mn atoms induced lattice distortion, vacancy defects, changed the electronic structure and microscopic morphology of NiSx . The alkaline electrolytic cell consisting of double Mn-NiSx electrode achieved a cell voltage of only 1.52 V at a current density of 10 mA/cm 2 . Abstract: The hydrogen is described as a clean and sustainable alternative to fossil fuels in numerous energy systems. Hydrolysis is an important method for high purity, high volume hydrogen production. In order to accelerate the kinetics of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in alkaline media, it is essential to explore efficient catalysts. In this paper, the nanoscale self-supported Mn-NiS/Mn-Ni3 S4 composite catalysts was assembled on nickel foam. Benefiting from the lattice distortion and vacancy defects caused by the doping of Mn elements, the catalysts exposed an increasing number of electrochemical surfaces and effective active sites, showing impressive electrochemical performance with a HER overpotential of only 94.2 mV at 10 mA/cm 2 and an OER overpotential of only 253 mV to drive 50 mA/cm 2 . Applying as the bifunctional catalysts, the Mn-NiS/Mn-Ni3 S4 couple only achieved a low voltage of only 1.52 V to drive 10 mA/cm 2 . This paper provides new ideas and references for the rational design of high-performance sulfide catalysts with non-precious metal composites.